Interaksi-Dialogis Mazhab Tafsir UIN Imam Bonjol Padang - Toni Markos; Mhd Idris; Muhammad Hanif; Agym Sayyidar Rusli (Jurnal Ulunnuha, 2023)
This study aims to determine the research methods and issues discussed by graduates of the Qur'an and Tafsir Study Program and their relation to the development of dialogue-interaction science as the philosophical foundation of the scientific paradigm of UIN Imam Bonjol Padang. This research is a qualitative literature research. The primary data of this research is the results of research by students of the Qur'an and Tafsir Study Program for the 2017 and 2018 batches because these two generations have graduated since the change in the philosophical foundation of the scientific paradigm of UIN Imam Bonjol Padang, namely interaction-dialogical. While the secondary data obtained from the literature related to the research discussion. The data analysis method used is the content analysis method. The results of this study indicate that the method used by students of the Qur'an and Tafsir Study Program in completing the thesis is dominated by literature review as much as 69% with a total of 104 thesis titles and a field study of 31% with a total of 46 thesis titles. The interpretation method that is widely used is the maudhu'i interpretation method for library research and the living qur'an for field studies. while the issues most written by students were social and cultural issues as much as 55% of the total research. This proves that the interactions of the scientific studies of the Qur'an and the interpretation of the Qur'an and Tafsir Study Programs interact more and have dialogue with the social sciences. For this reason, the Al-Qur'an and Tafsir Study Program has been able to develop science that is not only based on normative-orthodox or textual-normative turats (traditions), but has also been able to dialogue with scientific development and local culture. So that the principles and scientific foundations of the dialogue-interaction have been imprinted in the graduates and scientific works of graduates of this study program.